2017
DOI: 10.1371/journal.pone.0180185
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices, beliefs, and social norms in low-resource communities in Mexico: Insights for how to improve future promotion strategies

Abstract: IntroductionBreastfeeding is recommended exclusively for the first 6 months after birth, with continued breastfeeding for at least 2 years. Yet prevalence of these recommendations is low globally, although it is an effective and cost-effective way to prevent serious infections and chronic illness. Previous studies have reported that social support greatly influences breastfeeding, but there is little evidence on perceived social norms in Mexico and how they affect actual behavior.ObjectiveOur objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 50 publications
6
61
1
8
Order By: Relevance
“…The primary obstacles reported for breastfeeding in this study aligns with results of previous research from the region (12,(18)(19) and other populations (20)(21). Even though they had the option of adding another obstacle that was not listed, all the participants who reported having some di culty with breastfeeding selected one of the 10 options presented.…”
Section: Discussionsupporting
confidence: 84%
“…The primary obstacles reported for breastfeeding in this study aligns with results of previous research from the region (12,(18)(19) and other populations (20)(21). Even though they had the option of adding another obstacle that was not listed, all the participants who reported having some di culty with breastfeeding selected one of the 10 options presented.…”
Section: Discussionsupporting
confidence: 84%
“…In general, we could observe that the age and education years explained the myth scores, especially for certain myths. For example, younger participants in our study, women with the lowest levels of education and lower socioeconomic status, and fewer previous pregnancies were most likely to believe that "a frightened or angry mother should not nurse a baby" and "drinking atole or beer enhances maternal milk production", as showed by Swigart et al, in low-income communities in Mexico [36]. On the other hand, it has been reported that older mothers held fewer myths; the reason may be due to that they have more experience [10].…”
Section: Myths About Nutrition and Diet During Breastfeedingsupporting
confidence: 49%
“…Promotion of breastfeeding needs multilevel supportive measures with interventions being implemented through several channels [ 17 ]. Fathers have been named as one recommended target in promoting breastfeeding [ 22 , 23 ]. Qualitative research findings have revealed some domains of the father’s role in breastfeeding [ 24 ].…”
Section: Introductionmentioning
confidence: 99%